Digitization of Administration in Poland on the Example of Services Rendered by the Social Insurance Institution (ZUS) - Świątek, Władysław (Scientific Journal of Bielsko-Biala School of Finance and Law, 2022)
The development of information society and continuous demand for fast and efficient administration services rendered for the benefit of citizens call for constant improvement of e-services and automation processes in administrative formalities. This paper evaluates services rendered by public administration based on E-Government Digital Index and then presents online services provided by the Polish Social Insurance Institution (ZUS). The paper also reviews ZUS development strategy for 2021-2025 which is supposed to lift the burden incumbent on the social security premium payers, to fast forward dealings related to administrative matters and, finally, to seal the public finance.